Industri Obat Halal di Indonesia Antara Peluang dan Tantangan - Feffi Azzainatus Syaffira; Oman Fathurohman SW (An-Najat, 2024)
The halal medicine industry in Indonesia faces significant challenges related to the implementation of the Halal Law (UU Halal). Key challenges include distribution and supply chains, as well as compliance with international standards. The application of the halal label can disrupt the domestic drug distribution system, while almost all imported drug active ingredients do not have halal certification. The Halal Law also has the potential to disrupt the investment climate in Indonesia. To overcome this, Indonesia's general initiative needs to establish halal standards that are efficient and consistent with international standards. The government must comply with halal standards regulated in the Codex Alimentarius as part of Indonesia's commitment to the TBT Committee at the WTO. The absence of implementing regulations such as Presidential Regulations (PP) and Ministry of Religion Regulations (PMA) creates legal uncertainty. The practical challenges of implementing the Halal Law are very complex because halal certification will face industry players, most of whom do not wish to obtain halal certification. Digital technologies such as HalalChain, Halal Trail, and HalalGuide can help in verifying and ensuring halal certification compliance. Blockchain, which is often considered a revolutionary technology, can provide transparency and accountability in the halal certification process. The use of this technology can make it easier to verify the validity of halal certification and help Indonesia become a global leader in halal certification.